A Development of an Interactive Web-Based Video Information System Learning Module - Rompas, Parabelem T. D.; Wowor, Christaria; Lengkong, Chifly Chandra; Karel, Lordy; Batmetan, Johan Reimon (International Journal of Information Technology and Education, 2025)
This study aims to develop an interactive web-based video learning module for the Information Systems course in the Information and Communication Technology Education (PTIK) Study Program at Manado State University. The research seeks to address the need for innovative, flexible, and engaging learning resources that support independent learning and improve students’ understanding of Information Systems concepts. Specifically, the study focuses on producing a valid, practical, and effective multimedia-based learning module that integrates web technology and interactive video features.The research adopts a Research and Development (R&D) methodology using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. At the analysis stage, learning needs, curriculum demands, and student characteristics were assessed. The design stage involved planning the module structure, interactive video storyboard, and interface. The development stage produced the web-based module and interactive videos, which were then validated by media and material experts. Implementation was carried out through limited trials with students, while evaluation assessed feasibility, usability, and effectiveness.The results indicate that both media experts and material experts rated the module as “Very Good,” with overall validity scores exceeding 90%. Students reported increased motivation, engagement, and improved conceptual understanding when using the module. The interactive elements—such as quizzes, visualizations, and navigation features—were particularly effective in enhancing comprehension.In conclusion, the interactive web-based video module is feasible, effective, and aligned with digital-native learning needs. It provides a valuable alternative learning resource that supports student-centered learning and improves the quality of Information Systems education.